MELAWAN STIGMA RADIKAL: STUDI GERAKAN PEREMPUAN BERCADAR DI INSTAGRAM - Muhammad Ridha Basri (Aplikasia: Jurnal Aplikasi Ilmu-ilmu Agama, 2021)
Humans can adjust the way they dress to manage information about their identity. Veiled women in Indonesia often experience negative stigmatization and discrimination. This is due to the fact that the veil is close to the purification of Islam, the appearance of radical Islamic identity, and events of terrorism. Some of these casuistic facts are often generalized to all veiled women. This study looks at the response of a group of veiled women on Instagram in responding to terrorism cases in front of the Makassar Cathedral Church and at the Jakarta Police Headquarters at the end of March 2021, the perpetrators involving veiled women. Instagram has given birth to a new reality in expressing religious beliefs. This research using virtual ethnography method shows about a group of veiled women who use Instagram to display a positive image. The results of observations on several Instagram accounts of women with veils, it appears that this symptom is a form of expression of popular Islamic culture which has moderate and restless views with a negative stigma on the clothes they wear. Through texts, photos and videos uploaded to Instagram, they narrate their open views and do not want to be associated with radicalism. When there are terrorism cases involving women who wear the veil, they are more active in uploading an explanation that the veil is not a radical identity.